2016
DOI: 10.1016/j.bjid.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and clinical features of Mycoplasma pneumoniae infection in neonates

Abstract: Mycoplasma pneumoniae could be an important etiologic agent for respiratory tract infection in neonates. In neonates Mycoplasma pneumoniae infection was usually associated with older age, presence of fever, and less tachypnea. Mycoplasma pneumoniae infection in neonates tends to be a mild process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…There were variations in the positive rate of M pneumoniae infection according to age; it was usually high for children and adolescents [1,2,8,14,15] and low for infants and adults. [2,8,[16][17][18] For the child population, most studies have reported a higher positive rate for children aged > 5 years than for those < 5 years old [1,2,[18][19][20] ; the same result was observed in our study, which showed that children under the age of 6 years had the highest infection rate, which is thought to be related to incomplete immune mechanisms in this group and was easily infected by M pneumoniae. [5,21] Some studies have shown sex differences in M pneumoniae infections, [1,5,22,23] with some showing no differences.…”
Section: Discussionsupporting
confidence: 88%
“…There were variations in the positive rate of M pneumoniae infection according to age; it was usually high for children and adolescents [1,2,8,14,15] and low for infants and adults. [2,8,[16][17][18] For the child population, most studies have reported a higher positive rate for children aged > 5 years than for those < 5 years old [1,2,[18][19][20] ; the same result was observed in our study, which showed that children under the age of 6 years had the highest infection rate, which is thought to be related to incomplete immune mechanisms in this group and was easily infected by M pneumoniae. [5,21] Some studies have shown sex differences in M pneumoniae infections, [1,5,22,23] with some showing no differences.…”
Section: Discussionsupporting
confidence: 88%
“…In China, several studies investigate the prevalence of M. pneumoniae in CAP. Data have shown that M. pneumoniae infection accounted for 6.7% of CAP cases in neonates, 40.8% in children, and 18.8% in adults, respectively. All these indicated that M. pneumoniae remains one of the most common causes of CAP.…”
Section: Introductionmentioning
confidence: 99%